In vivo expression of mammalian BiP ATPase mutants causes disruption of the endoplasmic reticulum. - Hendershot, L M (1995)
BiP possesses ATP binding/hydrolysis activities that are thought to be essential for its ability to chaperone protein folding and assembly in the endoplasmic reticulum (ER). We have produced a series of point mutations in a hamster BiP clone that inhibit ATPase activity and have generated a species-specific anti-BiP antibody to monitor the effects of mutant hamster BiP expression in COS monkey cells. The enzymatic inactivation of BiP did not interfere with its ability to bind to Ig heavy chains in vivo but did inhibit ATP-mediated release of heavy chains in vitro. Immunofluorescence staining and electron microscopy revealed vesiculation of the ER membranes in COS cells expressing BiP ATPase mutants. ER disruption was not observed when a "44K" fragment of BiP that did not include the protein binding domain was similarly mutated but was observed when the protein binding region of BiP was expressed without an ATP binding domain. This suggests that BiP binding to target proteins as an inactive chaperone is responsible for the ER disruption. This is the first report on the in vivo expression of mammalian BiP mutants and is demonstration that in vitro-identified ATPase mutants behave as dominant negative mutants when expressed in vivo.